2018
DOI: 10.1080/23311908.2018.1554773
|View full text |Cite
|
Sign up to set email alerts
|

Innovative computer technology in music-based interventions for individuals with autism moving beyond traditional interactive music therapy techniques

Abstract: Autism spectrum disorders are characterised through impaired development in social interaction, communication and repetitive behaviours and interests (American Psychiatric Association, 2013). The condition is heterogeneous, and despite these symptoms being commonly identified with ASD, the extent of these difficulties are unique to the individual (Lord, Cook, Leventhal, & Amaral, 2000). Commonly, children with autism can experience complications in tactile, visual and auditory processing, with over 96% of chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 123 publications
(127 reference statements)
1
8
0
Order By: Relevance
“…The children with autism have characteristics of difficult to focus, get bored quickly, and unable to control unwanted motoric movement (Al Irsyadi & Rohmah, 2017). Usually, the autism children did not only have one disorder, but a complication of sensory, vision and hearing problems (Johnston et al, 2018). The symptoms of Autism Spectrum Disorder (ASD) generally appeared in the beginning stage of children growth (Shabbir et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The children with autism have characteristics of difficult to focus, get bored quickly, and unable to control unwanted motoric movement (Al Irsyadi & Rohmah, 2017). Usually, the autism children did not only have one disorder, but a complication of sensory, vision and hearing problems (Johnston et al, 2018). The symptoms of Autism Spectrum Disorder (ASD) generally appeared in the beginning stage of children growth (Shabbir et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…A significant place in this technique is also occupied by listening to music, mostly folk songs in the native language (especially effective is listening if the child's mother sings). Johnston et al 2018 [13] also hold this viewpoint. As noted in their study, "fundamental elements of music have been shown form social relationships and promote cognitive progression," and also "motivate children to interact differently with their environment through providing novel and engaging approaches to music interaction and creativity" [13].…”
Section: Literature Reviewmentioning
confidence: 93%
“…Future directions of digital transformation are being explored in education as a result of advancement in information technology [39,40]. The rapid development of technology and its success in other areas has led most educators to become more positive about technology-enabled education [41,42]. In terms of faculty readiness to choose technology in teaching before the pandemic, most teachers preferred to follow traditional teaching strategies and maintain their old instructing habits when unfamiliar with virtual tools [43].…”
Section: Characteristic Of General Online Learning and Teaching That ...mentioning
confidence: 99%